Understanding Student Engagement with Mobile Learning: A Structural Model for Interactive Education in Vietnam - Tang, Minh Dung; Nguyen Thi, Nga; Ta, Thanh Trung; Le Thai Bao, Thien Trung (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The factors that impact the willingness of Vietnamese secondary school students to embrace mobile learning are examined in this study using the framework of the technology acceptance model (TAM). The study utilized a quantitative research approach, and data were gathered accordingly from 611 students via structured questionnaires. The research focused on critical variables, including perceived usefulness (PU), perceived ease of use (PEU), perceived mobility (PM), social influence (SI), self-efficacy (SE), learning autonomy (LA), and perceived enjoyment (PE). Covariance-based structural equation modeling (CB-SEM) was utilized to analyze the relationships among these variables. The findings revealed that PU, PEU, and PE significantly affect students’ behavioral intention (BI) to adopt mobile learning. At the same time, external factors such as PM, SI, SE, and LA indirectly shape PU and PEU. These results deepen the understanding of mobile learning adoption within the Vietnamese educational context and underscore the need for targeted policy development to foster student engagement with mobile technologies. This study contributes to the broader educational technology literature, offering valuable insights for educators and policymakers aiming to optimize learning experiences through mobile platforms.